LPI Linux certification in a nutshell - Pritchard, Steven (In a nutshell (O'Reilly & Associates), 2006)
LPI Linux Certification in a Nutshell, Second Edition is an invaluable resource for determining what you needto practice to pass the Linux Professional Institute exams. This bookwill helpyou determine when you're ready to take the exams, which aretechnically challenging and designed to reflect the skills thatadministrators needin real working environments. As more corporations adopt Linux as the networking backbone for theirIT systems, the demand for certified technicians will becomeeven greater. Passing the LPI exams will broaden your career optionsbecause the LPICis the m.